Discourse and practice of participatory flood risk management in Belfast, UK. (April 2017) - Moon, Jonathan; Flannery, Wesley; Revez, Alexandra
Highlights: Paper evaluates participation in flood risk management in Belfast. Participatory mechanisms are shown to be tokenistic. Management process is characterised as adopting a resposibilisation approach. Agency responsibilities are ambiguous and need simplification. Recommendations are made for improved participation. Abstract: The introduction of the Floods Directive signals a move from flood protection towards flood risk management in the European Union. Public participation is highlighted in the Floods Directive as being instrumental to effective implementation of this new approach. This study utilised document analysis, non-participant observation, a questionnaire survey, and interviews to evaluate the discourse and practice of participation in the implementation of the Floods Directive in Belfast, United Kingdom. Flood risk management processes in Belfast are found to be high on participatory rhetoric but low on meaningful engagement. The participatory process is lacking in transparency, does not encourage the active participation of interested parties and has not been clearly communicated to key publics. Opportunities to increase meaningful public participation in the process remain underutilised, and the establishment of local flood forums has provided little opportunity for meaningful engagement. Some actions of governance agencies could be best characterised as facilitating the responsibilisation of risk and are designed to manage risk to agencies rather than address flooding issues.